(2x-5y)-(2x+4y) 去括号,并合并同类项.
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/03 20:10:25
(2x-5y)-(2x+4y)去括号,并合并同类项.(2x-5y)-(2x+4y)去括号,并合并同类项.(2x-5y)-(2x+4y)去括号,并合并同类项.=2x-5y-2x-4y=(2x-2x)-(
(2x-5y)-(2x+4y) 去括号,并合并同类项.
(2x-5y)-(2x+4y) 去括号,并合并同类项.
(2x-5y)-(2x+4y) 去括号,并合并同类项.
=2x-5y-2x-4y=(2x-2x)-(5y+4y)=-10y
等于2X-5Y-2X+4Y 等于-Y
(2x-3y)-(5x-y)去括号
(2x+3y)-(5x-y)去括号
整体去括号;化简[5(x-y)-3(x-y)-(x-y)+2(x-y)]-2(x-y)
整体去括号;[5(x-y)-3(x-y)-(x-y)+2(x-y)]-2(x-y)化简
3x-【(y-x)-2x-y】 去括号,
3x-2y-[-4x+(x+3y)]+y 去括号然后合并同类项,
去括号(4x-3y)-[-(3-x)+(x-y)]-5x 还是去括号4xy²-3x²y-{3x²+xy²-[2xy²-4x²y+(x²y-2xy²)]}
(2x-5y)-(2x+4y) 去括号,并合并同类项.
5(2x-7y)-3(4x-10y) 去括号,再合并同类项,
去括号 5(2x-7y)-3(4x-10y)
去括号3(x-y)-2(2x-y)=
x-2(y-z)去括号=(
去括号 -(x-2y-z)=?
去括号并合并同类项(1)3x-2(x+7)+2(2x+5) (2)(4x-3y)-[-(3y-x)+(x-y)]-5x
1,5{2x-7y}-3{4x-10y} 2,{x-y}-[3x+{-x+y}] 去括号,合并同类项,
3x-(3x+4y)+(4x+2y)去括号,并合并同类项
(-4y+3)-(-5y-2)去括号去括号!
先去括号,再合并同类项.4x+(x-3y) -(2s-5)+6